The Henry semianalytical solution for saltwater intrusion with reduced dispersion - Zidane, Ali; Younes, Anis; Huggenberger, Peter; Zechner, Eric (Water resources research, 2012)
The Henry semianalytical solution for salt water intrusion is widely used for benchmarking density dependent flow codes. The method consists of replacing the stream function and the concentration by a double set of Fourier series. These series are truncated at a given order and the remaining coefficients are calculated by solving a highly nonlinear system of algebraic equations. The solution of this system is often subject to substantial numerical difficulties. Previous works succeeded to provide semianalytical solutions only for saltwater intrusion problems with unrealistic large amount of dispersion. In this work, different truncations for the Fourier series are tested and the Levenberg‐Marquardt algorithm, which has a quadratic rate of convergence, is applied to calculate their coefficients. The obtained results provide semianalytical solutions for the Henry problem in the case of reduced dispersion coefficients and for two freshwater recharge values: the initial value suggested by Henry (1964) and the reduced one suggested by Simpson and Clement (2004). The developed semianalytical solutions are compared against numerical results obtained by using the method of lines and advanced spatial discretization schemes. The obtained semianalytical solutions improve considerably the worthiness of the Henry problem and therefore, they are more suitable for testing density dependent flow codes. Key Points Salt water intrusion into a confined aquifer in the case of reduced dispersion New Henry's semianalytical solution for benchmarking density dependent flow codes Calculation of the Fourier series coefficients using the Levenberg‐Marquardt algorithm